Community needs-based prioritization of landscape restoration technologies in Basona-Worena and Doyo-Gena Woredas, Ethiopia - Getachew, Kibebework; Abera, Wuletawu; Belay, Tefera; Tamene, Lulseged; Teklay, Achenafi (Journal of Degraded and Mining Lands Management, 2025)
Land degradation in Ethiopia is a pressing issue that demands immediate attention. Although various sustainable land management options have been introduced through top-down approaches, farmers have shown low adoption rates. The objective of this research was to assess the community prioritization of landscape restoration technologies and the appropriation of ecosystem services in the Basona-Worena and Doyo-Gena woredas of Ethiopia. The evaluation of land management option tool was used to survey farmers' preferences and compare different land management options based on input, cost, perceived advantages, and potential drawbacks.Data from 64 participants revealed that farmers were interested in a wide range of benefits. However, their top three preferences were increased food supply, enhanced soil fertility, and improved water supply. The study emphasized the need for site-specific land management measures. Farmers in Basona-Worena favored terrace and bund practices, while farmers in Doyo-Gena preferred exclosure and agroforestry practices. Conversely, the propensity of terracing to attract rodents and pests, the lengthy time takes to see results from bunding, and the cost of gabions were among the shortcomings that farmers identify in conservation techniques. Terracing was the first option for supplying fundamental ecosystem services in both locations, followed by biological measures, water percolation pits, and bunds. All farmers ranked the business-as-usual option as their least preferred option because they perceived it to have limited potential for yielding desired benefits. These findings provide a robust model for informed decision-making on suitable restoration technologies, holding promise for landscape restoration initiatives in Ethiopia and similar locations worldwide.